Association Between Dietary Patterns and the Incidence of Hypertension in Adults - Rahimatul Uthia; Harum Lailatul Husna; Ira Oktaviani RZ; Fathul Jannah (JURNAL PROTEKSI KESEHATAN, 2026)
Hypertension is one of the major public health problems that may lead to serious cardiovascular complications if not properly managed. An unhealthy dietary pattern, such as high intake of sodium, fat, and carbohydrates, is a significant factor contributing to increased blood pressure. This study aimed to describe dietary patterns and the incidence of hypertension among patients at Limapuluh Health Center, Pekanbaru City. This descriptive study employed a cross-sectional approach. A total of 63 respondents were selected using an accidental sampling technique. Data were collected through interviews using a Food Frequency Questionnaire (FFQ) and blood pressure measurements, then analyzed univariately. The results showed that most respondents had poor dietary patterns (58.7%) and experienced grade 1 hypertension (50.8%) and grade 2 hypertension (33.3%). These findings indicate a tendency between poor dietary patterns and the high incidence of hypertension. Nutritional education and healthy lifestyle promotion are recommended to prevent hypertension in the community.